2020
DOI: 10.1037/pas0000824
|View full text |Cite
|
Sign up to set email alerts
|

A Multiple Indicators Multiple Causes (MIMIC) model of friendship quality and comorbidities in children with attention-deficit/hyperactivity disorder.

Abstract: The unique objectives of the current investigation were: (a) to assess the fit of a multiinformant 2-factor measurement model of friendship quality in a clinical sample of children with attention-deficit/ hyperactivity disorder (ADHD); and (b) to use a multiple indicators multiple causes approach to evaluate whether comorbid externalizing and internalizing disorders incrementally predict levels of positive and negative friendship quality. Our sample included 165 target children diagnosed with ADHD (33% girls; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Internal consistency in our sample for each informant was ␣ Ն .87 for positive and ␣ Ն .75 for negative friendship quality. Confirmatory factor analyses in the current sample found that a two-factor model (positive and negative friendship quality) with four indicators per factor (reports by the parent, child, friend, and parent of the friend) had good fit (Normand, Mikami, Savalei, & Guiet, 2020). Composite scores reflecting the mean of the four informants were created for positive and negative friendship quality.…”
Section: Methodsmentioning
confidence: 69%
“…Internal consistency in our sample for each informant was ␣ Ն .87 for positive and ␣ Ն .75 for negative friendship quality. Confirmatory factor analyses in the current sample found that a two-factor model (positive and negative friendship quality) with four indicators per factor (reports by the parent, child, friend, and parent of the friend) had good fit (Normand, Mikami, Savalei, & Guiet, 2020). Composite scores reflecting the mean of the four informants were created for positive and negative friendship quality.…”
Section: Methodsmentioning
confidence: 69%
“…Regarding child-related characteristics, difficulties with self-control when faced with challenges and a tendency toward arguing were both linked to bullying perpetration in our analysis of children with ADHD. Overall, these findings suggest that these two aspects of emotional regulation, which are associated with disruptive behavior disorders and represent common issues for those with ADHD (Arseneault et al, 2010; Fogler et al, 2022; Kaltiala-Heino et al, 2000; Normand et al, 2020; Unnever & Cornell, 2003), are important to consider when addressing bullying perpetration (Fite et al, 2014; Kokkinos & Panayiotou, 2004). Overall, the findings around emotional regulation issues and both BV and BP fit what is known around the particular type of aggression exhibited by those with ADHD, reactive aggression.…”
Section: Discussionmentioning
confidence: 89%
“…They may be unaware or may rely on others to identify if their child is a bullying victim or perpetrator. Future research integrating multiple informants may provide a more complete understanding of children's peer relationships (Normand et al, 2020). The survey also did not address whether children's current type of bullying involvement may be different from past involvement.…”
Section: Limitationsmentioning
confidence: 99%
“…Variable-centered approach have come under growing criticism for their possible inability to fully “capture the configurations of factors that collectively explain behavioral processes” (Bauer & Shanahan, 2007). A step beyond this is studies using exploratory factor analysis to yield two dimensions (positive and negative) that are then examined individually as indicators of friendship quality (e.g., Normand et al, 2020).…”
Section: Friendship Profilesmentioning
confidence: 99%